Digital Light Processing 3D-Printed Ceramic Metamaterials for Electromagnetic Wave Absorption - Zhou, Rui; Wang, Yansong; Liu, Ziyu; Pang, Yongqiang; Chen, Jianxin; Kong, Jie (Nano-Micro Letters, 2022)
Combining 3D printing with precursor-derived ceramic for fabricating electromagnetic (EM) wave-absorbing metamaterials has attracted great attention. This study presents a novel ultraviolet-curable polysiloxane precursor for digital light processing (DLP) 3D printing to fabricate ceramic parts with complex geometry, no cracks and linear shrinkage. Guiding with the principles of impedance matching, attenuation, and effective-medium theory, we design a cross-helix-array metamaterial model based on the complex permittivity constant of precursor-derived ceramics. The corresponding ceramic metamaterials can be successfully prepared by DLP printing and subsequent pyrolysis process, achieving a low reflection coefficient and a wide effective absorption bandwidth in the X-band even under high temperature. This is a general method that can be extended to other bands, which can be realized by merely adjusting the unit structure of metamaterials. This strategy provides a novel and effective avenue to achieve “target-design-fabricating” ceramic metamaterials, and it exposes the downstream applications of highly efficient and broad EM wave-absorbing materials and structures with great potential applications. Article Highlights: 1 A novel UV-curable polysiloxane precursor was synthesized with excellent UV curable performance and stability. 2 The polysiloxane can fabricate Si–O–C ceramic with complex geometry via digital light processing 3D printing. 3 The ceramic metamaterials show electromagnetic wave absorption with a low reflection coefficient and a wide effective absorption bandwidth even under high temperature. 4 It provides a novel and effective avenue to achieve “target-design-fabricating” ceramic metamaterials with potential in EM wave-absorbing structures from nano to micro scale.